Determinação das alterações biomecânicas de idosos caidores e não caidores submetidos a protocolo incremental de fadiga - Karuka, Aline Harumi [UNESP] (2014)
The aging process is accompanied by several changes in the neuromuscular system, which interferes with motor activities such as walking. These changes make the movement pattern less efficient, leading the individual to a faster fatigue onset and increasing the risk of falls in the elderly population. The aim of the present study was to analyze the effect of an incremental protocol fatigue on biomechanical gait variables during preference gait speed in elderly. The study included 22 female volunteers, aged 60-85 years, not institutionalized. Data collection was done in two days. On the first day volunteers were questioned about their fall history and use of drugs, Berg Balance Scale, Mini -Mental State Examination, protocol of preference gait speed determination and familiarization were performed. On the second day volunteers did the gait assessment, which was initially made in ground, followed by the incremental fatigue protocol on the treadmill and then the reassessing gait performance in ground. The gait assessment consisted in acquisition of EMG, kinematic and kinetic data during gait in preferred speed...